2022
DOI: 10.5861/ijrse.2022.331
|View full text |Cite
|
Sign up to set email alerts
|

Learning activity sheets using interactive formative assessment and feedback mechanism for grade 9 mathematics

Abstract: The demands in the education system, particularly the adoption of distance learning, vastly affected the teaching and learning and put a challenge in the conduct of assessment, including limitations in giving feedback. Hence, this quasi-experimental study developed Learning Activity Sheets (LAS) Using Interactive Formative Assessment and Feedback Mechanism and determined its effect on the Mathematics performance of Grade 9 learners at Bulan National High School, Bulan, Sorsogon. In the study, there was a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Based on this guideline, the importance of demonstrating and disseminating the applicability of formative assessment has emerged in order to improve success in mathematics teaching. In many international studies, it was reported that the formative assessment practices shaped the teaching practices by increasing student performance, that positive reflections were observed on students when teachers designed formative assessment practices effectively, that they were used to identify the gaps in learning, that the interactive formative assessments and feedback mechanisms contributed positively to students' understanding of the lesson, completing tasks, communication, interest in mathematics and social relations, and that the formative assessment approach increased students' success and metacognitive awareness compared to the traditional approach (Agwagah & Ezieke, 2023;Fatima, 2022;Hiloma & Briones, 2022;Martin et al, 2022;Miller, 2019;Wafubwa & Csikos, 2022). In the national sense, even though there are a small number of studies on formative assessment practices, some studies on pre-service teachers and other disciplines have been encountered.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this guideline, the importance of demonstrating and disseminating the applicability of formative assessment has emerged in order to improve success in mathematics teaching. In many international studies, it was reported that the formative assessment practices shaped the teaching practices by increasing student performance, that positive reflections were observed on students when teachers designed formative assessment practices effectively, that they were used to identify the gaps in learning, that the interactive formative assessments and feedback mechanisms contributed positively to students' understanding of the lesson, completing tasks, communication, interest in mathematics and social relations, and that the formative assessment approach increased students' success and metacognitive awareness compared to the traditional approach (Agwagah & Ezieke, 2023;Fatima, 2022;Hiloma & Briones, 2022;Martin et al, 2022;Miller, 2019;Wafubwa & Csikos, 2022). In the national sense, even though there are a small number of studies on formative assessment practices, some studies on pre-service teachers and other disciplines have been encountered.…”
Section: Introductionmentioning
confidence: 99%